Améliorer l'enseignement dans le supérieur - Iryna Hontarenko; Oksana Kovalenko
The article addresses the issue of identifying the most efficient methods for preparing and delivering university lectures. Despite being the oldest instructional approach, lectures remain widely employed in universities worldwide. However, recent pedagogical research by Ukrainian scholars has not fully explored this matter, hindering the development of practical guidelines for instructors aiming to organize and deliver effective lecture courses. The article aims to provide insights into best practices, methodologies, and strategies that contribute to the effectiveness of lectures, ultimately leading to improved educational outcomes in higher educational institutions. The following research methods were used to solve the assigned tasks: theoretical - analysis of scientific sources, pedagogical and teaching-methodical materials, comparison; empirical - generalization of pedagogical experience. The results are the following. In the article we underscore the significance of establishing learning objectives, precise timing and structuring, reducing content volume, outlining lecture notes, careful selection of examples, and the lecturer's adaptability. Additionally, the authors highlight the importance of understanding the main stages of delivering a lecture, recognizing the nuances of maintaining students' effective attention, and involving them in active learning practices. The article provides practical recommendations for lecturers based on the reviewed sources and the authors' experience, accompanied by precautionary remarks. These precautions include avoiding the simultaneous use of numerous types of illustrative material and an excess of visual aids such as PowerPoint presentations. Such practices can lead to cognitive overload, as different processing forms may interfere with one another. The present study has explored the challenges and opportunities of effective lecturing in higher education, drawing on the insights from the British and American literature review and the empirical data collected from Ukrainian lecturers and students. Moreover, the article endeavors to conduct a more methodical analysis of efficacious techniques for preparing lectures, encompassing the critical stages of presentation. Furthermore, the present study seeks to delve into the nuances of captivating students' effective attention and involving them through practices associated with active learning.